The Application in Enhancing Students’ Speaking Skills at Senior High School - L’niana Aulia Zuhri Dalimunthe; Zulfiana Herni (STUDI ARAB, 2025)
Speaking skills in Arabic language learning are essential as they involve fluency, vocabulary mastery, pronunciation, and sentence structure; however, conventional teaching methods still provide limited opportunities for students to practice actively. Therefore, this study aims to examine the effect of using the InShot application as an audio-visual learning medium on students’ maharah kalam at MAS SKB 3 Menteri Bingkat. This research employed a quantitative experimental method with a pre-test and post-test control group design, involving a sample of 37 students consisting of an experimental class and a control class. Data were collected through pre-test and post-test instruments and analyzed using validity, reliability, normality, and Independent Sample t-test analyses. The statistical results showed a significance value (Sig. 2-tailed) of 0.001 < 0.05, indicating a significant difference between the post-test results of the experimental and control groups. Thus, it can be concluded that the use of the InShot application as an audio-visual learning medium has a significant positive effect on students’ speaking skills, and its effectiveness is enhanced when accompanied by teacher supervision during the learning process.